Arte-educação e o ensino de química: o papel educativo da música - Paiva, Jackson Alves Rodrigues (2019)
The teaching of chemistry has been historically marked by the accusation of being difficult and of having little or no use for the daily life of the students. However, such perception can only be supported by cognitive prejudice, especially as a result of a teaching characterized as bookish, content based on memorization and resolution of exercise, with little or no link with the daily life of the students. However, it must be made clear that the teaching of Chemistry can be carried out in an attractive, pleasant and language capable of stimulating students' curiosity, making their teaching captivating, stimulating and emotional through the universal language of music. Therefore, the question of research thus appears: To what extent does the use of music as a didactic resource promote the improvement of Chemistry teaching in high school? This research started from the hypothesis that music, as didactic resource, potentiates the improvement of the teaching of the contents of Chemistry in high school. Thus, thegeneral objective of this work is to analyze music as didactic resource in the improvement of the teaching of Chemistry in high school. From this general objective, the following specific objectives result: to analyze the relationship between aesthetics and education and teaching; to explain the relationship between art, education and teaching; to analyze the educational role of music in teaching chemistry. Music as a didactic resource in chemistry teaching consistsof a media containing copyrighted songs,in which the main chemicals topics are presented in musical format, with different musical genres, to help teachers and students to study chemistry in a more playful way. The collection of these media consists of the educational product. This research takes the form of a qualitative analysis, using the deductive and inductive methods. As data collection techniques, twoquestionnaires were applied as pre-test and post-test. In addition, a field diary and a semi-structured interview were used to support the qualitative analysis. The subjects of the research are 44 students from the 3rd series of the Administration Course of a State School of Vocational Education, located in the municipality of Caucaia in the state of Ceará.The research resulted in the ratification that the use of musicalization of chemical themes not only promoted more participatory and interactive classes of students with the discipline of Chemistry, but also modified the distorted view that many students had of this discipline, to have it as the "most hated" in high school, being effective with regard to playfulness, dynamism and creativity, making learning chemistry more enjoyable.